ANXIETY AND DEPRESSION IN CANCER PATIENTS - A SURVEY IN MEDICAL ONCOLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL - Chiragh, Sadaf; Ahmed, Ishfaq; Jameel, Abid (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out frequency of anxiety and depression in cancer patients presenting to medical oncology department of a tertiary care hospital. Methodology: This cross sectional study was conducted from January 2018 to June 2018 in medical oncology unit, Hayatabad Medical Complex (HMC), Peshawar. One hundred patients suffering from various neoplastic diseases were selected with consecutive sampling. Hospital Anxiety and Depression Scale (HADS-14-item) was administered. Those with score 8-10 on HADS were considered borderline for anxiety or depression and those with score â‰¥11 were considered to have anxiety or depression. Results: Out of 100 patients, 45 (45%) participants were females and 55 (55%) were males. Mean age of patients was 47.57 years. Sixty five, (65%) patients showed predominant symptoms of anxiety and 61 (61%) patients had varying levels of depression. Conclusion: There is a high prevalence of both anxiety and depression among cancer patients. Therefore careful attention must be paid towards diagnosis and treatment of these morbidities in cancer patients.